Oracle high availability, disaster recovery, and cloud services : explore RAC, data guard, and cloud technology /: explore RAC, data guard, and cloud technology. ([2019]) - Kumar, Y. V. Ravi; Basha, Nassyam; K. M., Krishna Kumar; Sharma, Bal Mukund; Kerekovski, Konstantin
No abstract available